Penerapan Metode Kooperatif Investigasi dalam Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - YUSLIDARTI, YUSLIDARTI (Komunitas Manajemen Kompetitif, 2018)
The purpose of this study is to determine whether cooperative learning Investigation can improve learning outcomes Mathematics students class V SD Negeri 002 Penghidupan Year 2016, the method used in this study is Classroom Action Research (PTK). This TOD uses an investigative learning model. The sequence of classroom action research steps are: planning, action, observation, and reflection. The results showed: 1. By using the model of investigative learning, student learning outcomes reached the average grade 81.55 and learning completeness reached 95.45% and increased in the second cycle reached 85.75% learning completeness reached 100%. Activity of students in following learning in the first cycle reached 59.09% in the second cycle increased to 95.45% while for learning activities in the first cycle group reached 79.54% and then in cycle II to 100%.